Palliative social media. Issue 1 (1st March 2014) - Taubert, Mark; Watts, Gareth; Boland, Jason; Radbruch, Lukas
Abstract: The uses of social media have become ubiquitous in contemporary society at an astonishingly fast-paced rate. The internet and in particular platforms such as Facebook, Twitter and YouTube are now part of most people's vocabulary and are starting to replace many face-to-face interactions. The online world, in particular, is alive with discussions, comments and anecdotes about the topics of illness, disease, hospitals, death and dying. The topic of death and dying had in the not too distant past been seen as taboo, but willingness and need to talk openly about it appears to be on the increase. In parallel to this, many public awareness campaigns are highlighting society's need to be more prepared for dying and death. This will have a significant impact on the way terminally ill patients and their families approach the last years, months and weeks of their lives and how they might expect palliative health and social care professionals working with them through these difficult periods to interact with them. We pay particular attention to the areas of digital posterity creation and memorialisation within the wider holistic context of end-of-life care.